Achieving urban water conservation: testing community acceptance - Snodgrass, Robert Warren, author; Hill, Duane W., author; Colorado Water Resources Research Institute, Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1977)
Employing a Q-Sort Factor Analytical Design, this study sought to develop a system for parametric representation of non-linear data structures using data acquired from representative samples of entire communities. The representations are specified in terms of a spatial metric "social space," an analog of psychological space. The defined social space is then characterized and used to define the community action zone which is hypothesized to a zone of community acceptance for those policies falling within its bounds. Such a zone for the communities of Lafayette and Louisville, Colorado was used to define socially and politically feasible water conservation policies for the communities. Policies with the highest feasibility for acceptance were legal restrictions on water use and restrictions on growth and development. The next most feasible were horticultural techniques and economic solutions. Reuse for agricultural purposes also appeared to have some political feasibility. This study demonstrated the usefulness of survey research in delineating viable water conservation programs.
Submitted to Office of Water Research and Technology, U.S. Department of Interior.
September 1977.
Keywords: Water conservation -- Public opinion